Penguatan Literasi Kewarganegaraan Melalui Pendidikan Politik di Kalangan Mahasiswa PPKn - Kothen, Sanctissima Trinitas Gute; Sae, Brampi Soniman; Ora, Inriwati Soniman; Toga, Tropina Kareri Hara (Paedagogie, 2025)
This study aims to analyze the role of political education in strengthening civic literacy among PPKn (Civic Education) students through dialogic, analytical, and issue-based learning practices. A descriptive qualitative approach was employed, utilizing document analysis, indirect observation, and literature review to examine the effectiveness of political education implementation within the higher education context. The findings indicate that the integration of political education into the curriculum, the use of discussion-driven and case-based instructional strategies, and student engagement in co-curricular activities significantly enhance analytical capacities, broaden conceptual understanding of citizenship, and foster critical and reflective civic dispositions. Moreover, students’ participation in deliberative forums and student organizations enriches their political experience, thereby contributing substantively to the development of their civic literacy. The study concludes that issue-based political education, when supported by a democratic and participatory academic environment, plays a significant role in advancing students’ comprehensive civic literacy. The study recommends the development of curricula that are responsive to socio-political dynamics, the strengthening of participatory pedagogical approaches, and the cultivation of a campus ecosystem conducive to democratic practices and active civic participation.